2011
DOI: 10.3177/jnsv.57.123
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lipid Accumulation in Liver and White Adipose Tissue in Aging in the SAMP10 Mouse

Abstract: SummaryThe population of elderly persons has increased worldwide. However, few studies have examined age-dependent changes in lipid and carbohydrate metabolism related to age-related diseases. The number of cases of metabolic syndrome is increasing worldwide and prevention of lifestyle diseases may lead to prolongation of lifespan. In this study, we examined age-dependent changes in lipid and carbohydrate metabolism in the senescenceaccelerated (SAM) P10 mouse. Tissue weights and biochemical parameters in plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…3B and C). In addition, increased plasma insulin levels have also been observed in senescence-prone (SAMP10) mice and reported to explain the increased lipid accumulation with age in these mice [11]. However, since cytokines have been demonstrated to regulate CD36 expression at the transcriptional level [37], the possibility also arises that increased cytokine levels during hepatic inflammation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3B and C). In addition, increased plasma insulin levels have also been observed in senescence-prone (SAMP10) mice and reported to explain the increased lipid accumulation with age in these mice [11]. However, since cytokines have been demonstrated to regulate CD36 expression at the transcriptional level [37], the possibility also arises that increased cytokine levels during hepatic inflammation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…But, to the extent of our current knowledge, no record on HFD-fed SAMP8 mice to study NAFLD is available. However, two recent studies compared HFD intake with standard chow feeding on hepatic changes in SAMP10) [23,24]. Their results showed that high-fat diet promoted lipid droplets accumulation in the livers of SAMP10 mice, contrary to normal chow feeding [23].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the SAMP10 mouse is widely used for analysis of mechanisms of aging (Shimada et al 2006;Unno et al 2007;Sasaki et al 2008;Tsuduki et al 2011;Honma et al 2011). In our previous study, we showed that SAMP10 mice fed a standard diet exhibited age-dependent increases of liver hydroxysteroid 11-beta dehydrogenase 1 (Hsd11b1) mRNA level, which promoted insulin secretion and insulin resistance and caused hyperinsulinemia and lipid accumulation in liver and white adipose tissue (Paterson et al 2004;Honma et al 2011). Hsd11b1 converts inert 11-dehydrocorticosterone into active corticosterone (Paterson et al 2004).…”
Section: Introductionmentioning
confidence: 99%